Inventarisasi Hama dan Penyakit pada Bibit Lima Jenis Tanaman Buah Tropis di Persemaian Mentawir - Saud, Oshlifin Rucmana; Syarifudin, Achmad; Nugroho, Andi; Saud, Oshferlia Rucmana; Utami, Widia Sri (Universitas Pattimura, 2025)
The nursery phase represents a critical early space in plant cultivation, which is highly susceptible to pest and disease incidence. Mentawir Nursery, as one of the largest seedling centers in East Kalimantan, plays a strategic role in supporting reforestation programs, including for Indonesia’s new capital city (IKN). This study aims to identify and document the types of pests and diseases affecting five tropical fruit crops, as well as to analyze the incidence and severity. The five plant species observed in this study are Citrus sinensis, A. integer, Psidium guajava, Mangifera indica, and Dimocarpus longan. The research method employed is Simple Random Sampling, with observations conducted on 20 individuals from each plant species. The collected data include attack levels, symptoms, and signs of pest and disease infestations.The results indicate that four plant species experienced a 100% attack frequency, while one species had an 80% attack rate. The severity of the attacks ranged from moderate to severe. The observed disease symptoms included leaf spots, leaf blight, loss of leaf tissue, internal leaf tissue loss, leaf tumors, and leaf curling. Identified infestation signs included the presence of whiteflies (Hemiptera), larvae (Diptera), small beetles (Coleoptera), as well as larvae and pupae (Lepidoptera).These findings serve as a basis for pest and disease management at Mentawir Nursery to enhance seedling success and plant productivity.